Pemanfaatan Media Loose Part dalam Meningkatkan Kemampuan Sains Permulaan Anak Usia 4-5 Tahun Di KB Plus Al-Furqon Ciomas Bogor - Listiana, Intan; Rahayu, Wening; Kasih, Delina (Neolectura, 2025)
This study aims to determine the process of improving early science skills through loose part media in children aged 4-5 years at KB Plus Al-Furqon Ciomas Bogor. The type of research conducted is Classroom Action Research (CAR). With the research subjects were 11 children aged 4-5 years at KB Plus Al-Furqon Ciomas Bogor. This study uses the Kemmis and Mc Taggart action model, the study was carried out in two cycles. The results of the study showed a significant increase in children's early science skills. This can be seen from the increase in the initial conditions of the cycle, namely from 16% to 50%, from cycle I to cycle II there was an increase in early science skills by 34%, namely from 50% to 84%. Children's early science skills before the action was carried out using loose part media, namely 9 out of 11 children had not yet shown their initial science skills. The increase in children's early science skills after the classroom action using loose part media was very large, this can be seen from the increasing percentage value, getting better and more satisfying.